2003
DOI: 10.1152/jn.00708.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of V1 Neural Responses to 2D Moving Patterns Depends on Receptive-Field Structure in the Marmoset Monkey

Abstract: A plaid pattern is formed when two sinusoidal gratings of different orientations are added together. Previous work has shown that V1 neurons selectively encode the direction and orientation of the component gratings in a moving plaid but not the direction of the plaid itself (Movshon et al. 1985). We recorded the responses of 49 direction-selective neurons to moving gratings and plaid patterns in area V1 of the anesthetized marmoset monkey (Callithrix jacchus). The responses of V1 neurons to rectangular patche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 15 publications
3
58
1
Order By: Relevance
“…However, most MT neurons do not construct the type of velocity-space representation hypothesized by these models (Majaj et al, 1999;Priebe et al, 2003). Models that rely explicitly on local measurement of terminator motion have also been proposed (Lorenceau et al, 1993;Rubin et al, 1995;Grossberg et al, 2001) and appear to be qualitatively consistent with recent V1 data (Pack et al, 2003;Tinsley et al, 2003).…”
Section: Integration Of Motion Signals In Mtmentioning
confidence: 93%
“…However, most MT neurons do not construct the type of velocity-space representation hypothesized by these models (Majaj et al, 1999;Priebe et al, 2003). Models that rely explicitly on local measurement of terminator motion have also been proposed (Lorenceau et al, 1993;Rubin et al, 1995;Grossberg et al, 2001) and appear to be qualitatively consistent with recent V1 data (Pack et al, 2003;Tinsley et al, 2003).…”
Section: Integration Of Motion Signals In Mtmentioning
confidence: 93%
“…SU and LFP responses to gratings and plaids were classified according to the Z-transformed partial correlation coefficients between the data and the component and pattern predictions (Tinsley et al, 2003;Smith et al, 2005) using the following equations (shown for the z-transformed pattern correlation):…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1b shows hypothetical tuning curves for a component-selective (dashed line) and pattern-selective (solid line) neuron. We categorized each neuron in our sample as pattern or component selective, using standard statistical criteria (Tinsley et al, 2003;Smith et al, 2005) (see Materials and Methods), and Figure 2a-c shows the resulting distributions for areas V1, MT, and MST. Here, blue dots represent component-selective neurons, red dots represent pattern-selective neurons, and black dots represent neurons that could not be assigned statistically to either category.…”
Section: Single-unit Pattern Selectivity Along the Dorsal Visual Pathwaymentioning
confidence: 99%
“…Pattern cells have been reported in striate cortex (V1) of the awake monkey (9%) [Guo et al, 2004], although the same experiment conducted on anesthetized animals (monkeys and cats) supported previous reports demonstrating an absence of pattern cells, thus highlighting the potential importance of feedback from other neural areas. In addition, investigations into the receptive fields of V1 neurons in the monkey have suggested that properties such as end-stopping [Pack et al, 2003] and broad tuning, which would enable feature tracking [Tinsley et al, 2003], may allow V1 to contribute directly to pattern motion perception. Pattern cells have also been reported in monkey V3, an extrastriate visual area intermediate in the visual processing hierarchy between V1 and MT [Gegenfurtner et al, 1997].…”
Section: Introductionmentioning
confidence: 99%